Analisis Kesediaan Menerima (WTA) Sebagai Proksi Pembayaran Jasa Lingkungan Air Di Pekon Datar Lebuay Kecamatan Air Naningan Kabupaten Tanggamus - Fatimah, Siti; Wulandari, Christine; Herwanti, Susni (Jurnal Sylva Lestari, 2016)
Payment for Environmental Services (PES) incentive need be applied to ensure the promotion of soil and water conservation. It's pro conservation attitude should be soon adopted by sharecroppers in various protected areas. Likewise the sharecroppers in Protected Forest Management Unit (KPHL) Batutegi which their area has been degraded. Based on the paper plan of Unit Pelaksana Teknis Daerah (UPTD) KPHL Batutegi (2014), there were critical area of 14405.10 hectares (24.77%) and very critical of 45.56 ha (0.77%). The value of the willingness to accept (WTA) for the water PES for upstream community as a provider of environmental services was necessary to be studied towards to increase willingness of people to apply soil and water conservation. The purposes of this study were to determine the water PES WTA value of Datar Lebuay Villages and establishment of influenced factors. The methods used in this research were WTA survey include gathering data as follows education, income, age, acreage (land tillage), number of trees and stay duration. The data was analyzed by double linear regression to examine the effect of these variables the WTA value. Based on the analysis, it could be concluded: a. The estimated water PES WTA value Datar Lebuay Villages was about 4119.05/tree/year averagely and the total water PES WTA value was Rp 14,033,050/year when the 3,682 trees belong to the communities, b. Factors that significantly affected the WTA value were age, stay duration and level of education. According to research results, it's suggested to scalling up this research to another village included add socio-economic factors such as gender, ethnicity and the other social variables. Keywords: Datar Lebuay Villages, payment for environmental services, Way Sekampung Sub-Watershed, WTA